Maxillary Sinus Assessment: A Computed Tomography Analysis and Classification - Mohammad Waheed El-Anwar; Mohamed Kamel Alawady; Hoda Ismail Abdelhamid; Tamer Oraby; Mohamed Talaat Albasiouny; Ashraf El-Hussiny (International Archives of Otorhinolaryngology)
Introduction The preoperative assessment of the computed tomography (CT) characteristics of the maxillary sinus helps to preserve its anatomical and functional integrity during and after surgery.